Peningkatan Kemampuan Berpikir Kritis dengan Model Problem Based Learning (PBL) Pada Mata Pelajaran Ekonomi Siswa Kelas X-6 di SMA Negeri 1 Porong Tahun 2022/2023 - Andeline, Putricya; Dewi, Retno Mustika; Sarirejo, Sarirejo; Suryani, Nina Dwi (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This research is motivated by economic learning applied by teachers who have not maximized students' critical thinking abilities. The low critical thinking ability of students is caused by the learning that is given only contains examples and practice questions. The purpose of this research is to improve students' critical thinking skills with the Problem Based Learning model. This research is a Collaborative Classroom Action Research conducted in 3 cycles. The subjects in this study were students of class X-6 at SMAN 1 Porong, which consisted of 36 students. The instruments used were pre-test, post-test, and observation sheets. The data were then analyzed qualitatively and quantitatively. The results showed that students' critical thinking skills increased with the Problem Based Learning model. In cycle I it was 71.53%, in cycle II it increased to 82.81%, in cycle III it increased to 88.37%, and in the final test it increased to 91.67%. So that the Problem Based Learning learning model can be applied in economics subjects and in other subjects.